2018
DOI: 10.18203/2320-6012.ijrms20180282
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bone mineral density among type 2 diabetes mellitus patients in western Odisha

Abstract: Background: Diabetes Mellitus is one of the most common chronic non-communicable diseases in the world. The relationship between type 2 diabetes mellitus (T2DM) and bone mineral density (BMD) has been controversial. Early identification of reduction in bone mass in a diabetic patient may be helpful in preventing the bone loss and future fracture risks. Objective: The aim is to study the effect of T2DM on BMD among patients in western Odisha.Methods: A cross-sectional study was conducted on 120 patients between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The association between T2DM and BMD is also controversial. Most studies showed decreased or unchanged BMD; however, some others revealed increased BMD [ 11 , 12 , 13 ]. Another diabetic complication contributing to detrimental bone effects is microangiopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The association between T2DM and BMD is also controversial. Most studies showed decreased or unchanged BMD; however, some others revealed increased BMD [ 11 , 12 , 13 ]. Another diabetic complication contributing to detrimental bone effects is microangiopathy.…”
Section: Introductionmentioning
confidence: 99%
“…We also could not find a significant association between duration of diabetes and BMD status. However, a number of studies found duration of diabetes to be significantly associated with BMD loss [10,11,13,19]. One of the reasons could be primarily the present study had only few cases with T2DM duration >10 years (mean duration of T2DM 6.21 years).…”
Section: Resultsmentioning
confidence: 79%
“…Association of BMD with glycemic status are controversial. In a recent report Thakur and Dash [13] found mean HbA1c of patients with low BMD to be significantly lower as compared to those having high BMD, thus showing good glycemic control to be associated with an increased risk of BMD loss. Conversely, they observed mean FBG of those with low BMD to be higher as compared to those having high BMD, thus painting just a reverse picture as observed for HbA1c.…”
Section: Resultsmentioning
confidence: 98%
“…A s a result, based on evidences that type2 diabetes mellitus can lead to poor bone quality and bone loss. Also, few studies have suggested that various bone indicators levels were found to be such as serum calcium, serum phosphorus and serum alkaline phosphate [17] . The hydrolytic enzyme alkaline phosphate is found in the liver, bile duct, kidney, intestinal mucosa, and placenta among other places many diabetics may also have been shown to have elevated levels of serum alkaline phosphatase [18] .…”
Section: Introductionmentioning
confidence: 99%